KETERAMPILAN METAKOGNISI SISWA DALAM PEMECAHAN MASALAH MATEMATIKA MATERI TRIGONOMETRI DI MAN 1 PONTIANAK - Sartika, Mas Tri; Zubaidah, Zubaidah; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to describe about student?s metacognition skill of mathematic problem solving on trigonoretry in MAN 1 Pontianak. The research method is descriptive with survey. The subjects of this research are five students grade XI MIPA 2 consist of two high students group, one middle students group, and two low students group in problem solving. The result of this research showed that students metacognition skills in the upper group in solving the problem, almost all indicators are met in each planning, monitoring, and evaluation. For students' metacognition skills in the middle group in problem solving is no better than the upper group in the planning process, monitoring process, and evaluation process. While the student?s metacognition skills in the lower group in problem solving, one students approach the metacognition skills of lower group students, while the other one students almost all the indicators are not fulfilled in each planning process, monitoring process, and evaluation process.Keyword : Metacognition Skill, Problem Solving, Trigonometry